Enzyme‐Cleavable Linkers for Protein Chemical Synthesis through Solid‐Phase Ligations. (14th July 2021) - Abboud, Skander A.; Amoura, Mehdi; Madinier, Jean‐Baptiste; Renoux, Brigitte; Papot, Sébastien; Piller, Véronique; Aucagne, Vincent
Abstract: The total synthesis of long proteins requires the assembly of multiple fragments through successive ligations. The need for intermediate purification steps is a strong limitation, particularly in terms of overall yield. One solution to this problem would be solid‐supported chemical ligation (SPCL), for which a first peptide segment must be immobilized on a SPCL‐compatible solid support through a linker that can be cleaved under very mild conditions to release the assembled protein. The cleavage of SPCL linkers has previously required chemical conditions sometimes incompatible with sensitive protein targets. Herein, we describe an alternative enzymatic approach to trigger cleavage under extremely mild and selective conditions. Optimization of the linker structure and use of a small enzyme able to diffuse into the solid support were key to the success of the strategy. We demonstrated its utility by the assembly of three peptide segments on the basis of native chemical ligation to afford a 15 kDa polypeptide. Abstract : A chemoenzymatic approach was developed for the synthesis of proteins by solid‐supported chemical ligation based on a tailor‐made phosphatase‐cleavable linker (see scheme). The size of the enzyme used directly correlates with the efficiency of the release of the synthesized protein. The method was applied to the synthesis of a 15 kDa polypeptide, the longest sequence ever synthesized through solid‐phase native chemical ligation.